2018
DOI: 10.1016/j.physa.2017.11.160
|View full text |Cite
|
Sign up to set email alerts
|

Different non-extensive models for heavy-ion collisions

Abstract: The transverse momentum (p T ) spectra from heavy-ion collisions at intermediate momenta are described by non-extensive statistical models. Assuming a fixed relative variance of the temperature fluctuating event by event or alternatively a fixed mean multiplicity in a negative binomial distribution (NBD), two different linear relations emerge between the temperature, T , and the Tsallis parameter q − 1. Our results qualitatively agree with that of G. Wilk. Furthermore we revisit the "Soft+Hard" model, proposed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
4
25
0
1
Order By: Relevance
“…which agrees with our previous work [21,22] and that of others [31]. T vs (q-1) in pp in pPb @ 5.02 TeV π in PbPb @ 2.76 TeV Note that the slope parameter T 1 in Table V turns negative and T 0 is nearly zero for the pp case, as discussed in [22]. Results of fittings on pion spectra, typically in pP b collisions at 5.02 TeV, fail in the obvious linear combinations probably due to the small mass of pions and high multiplicities.…”
Section: B Analysis Of the Pp B And P Bp B Resultssupporting
confidence: 94%
“…which agrees with our previous work [21,22] and that of others [31]. T vs (q-1) in pp in pPb @ 5.02 TeV π in PbPb @ 2.76 TeV Note that the slope parameter T 1 in Table V turns negative and T 0 is nearly zero for the pp case, as discussed in [22]. Results of fittings on pion spectra, typically in pP b collisions at 5.02 TeV, fail in the obvious linear combinations probably due to the small mass of pions and high multiplicities.…”
Section: B Analysis Of the Pp B And P Bp B Resultssupporting
confidence: 94%
“…By going towards more central nucleus-nucleus collisions, though the overall shape of the fitted distribution describes the experimental data, the Data/Theory plot shows an increasing 'oscillation' [37,38]. This is a known effect and needs further investigation, and it also might be an indication that for future studies, especially in central heavy ion collisions a more sophisticated soft+hard model might be more appropriate [29,95,103]. However, studying of this oscillation effect goes beyond the scope of this paper.…”
Section: Fitting Procedures and Performancementioning
confidence: 96%
“…During the investigation of the parameters, we showed that they possess non-trivial relations such as mass-and energy scaling [1,8]. There are also implications that for larger systems a soft-hard extension is needed [10,16]. These studies indicate that increasing the size of the colliding system (roughly speaking, the volume of the quark-gluon plasma) may also reflect in the parameters.…”
Section: Introductionmentioning
confidence: 90%
“…With the appearance of high precision experimental data spanning from low-to high-p T , neither the thermal models with a bare Boltzmann-Gibbs exponential distribution nor perturbative Quantum Chromodynamics (pQCD)-motivated power-law distributions are able to describe the whole spectrum. On the other hand, the Tsallis-Pareto distributions combine these two regions perfectly (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and references therein). During the investigation of the parameters, we showed that they possess non-trivial relations such as mass-and energy scaling [1,8].…”
Section: Introductionmentioning
confidence: 99%